PUSAT GREEN THERAPY INDONESIA TIMUR UNTUK PENANGANAN ANAK BERKEBUTUHAN KHUSUS - Haerul Syam; Rafelia Husain; Hayati, Riza Sativani (Prosiding Seminar Nasional Pengabdian Kepada Masyarakat, 2023)
Abstract This community service developed the East Indonesia Green therapy center and partnered with SADIQ. Green therapy, commonly known as nature therapy, is a method of stimulating children with special needs (ABK) using natural media. SADIQ has the potential to be developed as a Green therapy center for Eastern Indonesia: (1) it has implemented the Green therapy concept; (2) has sufficient open space; (3) has sunnah sports facilities that have potential for therapy; (4) have a good safety guarantee for the Green therapy program. The solutions offered for SADIQ to be developed as a Green therapy center include: (1) Green therapy education for SADIQ human resources in the form of training, practice and workshops; (2) provision of standard facilities to support the perfection of the types of stimulation services to be provided; (3) preparing a Green therapy service program starting from the name of the program to the stimulation activities that must be carried out; (4) preparation of Green therapy service program guidelines; (5) outreach and offering to the public and educational practitioners; (6) assisting the implementation of service programs at the Green therapy center. SADIQ is currently an alternative solution in providing ABK stimulation through natural media (green therapy). Abstrak Pengabdian masyarakat mengembangkan pusat Green therapy Indonesia Timur dan bermitra dengan Sekolah Alam Darul Istiqamah (SADIQ). Green therapy yang biasa dikenal dengan terapi alam merupakan salah satu metode stimulasi anak berkebutuhan khusus (ABK) menggunakan media alam. SADIQ memiliki potensi untuk dikembangkan sebagai pusat Green therapy Indonesia Timur: (1) telah menerapkan konsep Green therapy; (2) memiliki luas ruang terbuka yang cukup; (3) memiliki fasilitas olahraga sunnah yang potensial untuk therapy; (4) memiliki jaminan safety program Green therapy yang baik. Solusi yang ditawarkan bagi SADIQ untuk dikembangkan sebagai pusat Green therapy antara lain: (1) edukasi Green therapy kepada SDM SADIQ berupa pelatihan, praktik, dan workshop; (2) penyediaan fasilitas standar guna mendukung kesempurnaan jenis layanan stimulasi yang akan disediakan; (3) penyusunan program layanan Green therapy mulai dari nama program hingga kegiatan stimulasi yang harus dilakukan; (4) pembuatan panduan program layanan Green therapy; (5) sosialisasi dan penawaran kepada masyarakat dan praktisi pendidikan; (6) pendampingan implementasi program layanan di pusat Green therapy. SADIQ saat ini menjadi alternatif solusi dalam pemberian stimulasi ABK melalui media alam (green therapy).